1976
DOI: 10.1084/jem.143.6.1421
|View full text |Cite
|
Sign up to set email alerts
|

Cell interactions in the suppression of in vitro antibody responses.

Abstract: Initiation of humoral immune responses requires a complex series of interac-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 14 publications
3
13
0
Order By: Relevance
“…Durkin et al (23) demonstrated that low numbers of OVA-sensitized T memory cells added to higher numbers of lymph node cells from the same OVA-sensitized rats sometimes helped or potentiated and sometimes totally suppressed proliferative responses to either OVA or phytohemagglutinin. In the present studies, as was true of the earlier studies by others (20 -23), the mechanisms involved in the network(s) leading to help/potentiation or suppression of memory responses obviously are complex, involving other cells and mediators released by cells participating in the memory response and feedback loops (24,25).…”
Section: Discussionsupporting
confidence: 65%
“…Durkin et al (23) demonstrated that low numbers of OVA-sensitized T memory cells added to higher numbers of lymph node cells from the same OVA-sensitized rats sometimes helped or potentiated and sometimes totally suppressed proliferative responses to either OVA or phytohemagglutinin. In the present studies, as was true of the earlier studies by others (20 -23), the mechanisms involved in the network(s) leading to help/potentiation or suppression of memory responses obviously are complex, involving other cells and mediators released by cells participating in the memory response and feedback loops (24,25).…”
Section: Discussionsupporting
confidence: 65%
“…SRBC and TNP-CRBC were used as antigens. The preparation of TNP-CRBC has been described elsewhere (20), as have the controls for the effect of increased cell numbers on these responses (11). The procedure of mitogen stimulation of proliferation was done as described previously (21).…”
Section: Methodsmentioning
confidence: 99%
“…Experimental Protocol. As reported previously (11), immune spleen cells from adult mice primed 8 days earlier with SRBC and pertussis were put into Mishell and Dutton-type cultures with normal spleen cells from adult (greater than 10 wk) or young (3-21 days) animals. Duplicate cultures were assayed for direct and indirect plaque-forming cells (PFC) on days 4 and 5 by using a slide modification (19) of the Jerne plaque assay.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations